Balanço térmico de ovinos morada nova mantidos ao sol e à sombra semiárido brasileiro - Silva, Josinaldo Araújo da (2017)
In tropical regions the average radiant temperature (TRM) exerts a great influence on the heat balance of domestic animals, especially when the animals are located in regions near the equator (low latitude regions), since the radiation load in these localities occurs with a higher incidence of short waves. The objective of this study was to evaluate the thermal equilibrium of Morada Nova sheep in the shade and exposed to direct solar radiation, in a tropical semiarid environment. Ten adult sheep with an average weight of 32.76 ± 3.72 kg were used, distributed in two 10 x 10 Latin squares (10 days of records and 10 times). The ewes were evaluated from 7:00 am to 5:00 pm, the first group sheltered in the shade and the second group exposed to direct solar radiation. During the collections the sheep were taken to a containment trunk where they remained for all collection that was of 50 minutes for each animal. The rate of pulmonary ventilation (VE), respiratory rate (F), air temperature (Tar), vapor pressure (and [TE]), oxygen percentage (O2) of inspired air and carbon dioxide expired were quantified by means of an indirect calorimetry system using face mask. The heat balance of the animals was quantified according to the principles of the law of conservation of energy. A multivariate analysis of the environmental data and the physiological variables using SAS statistical software was done. According to the results, as the levels of solar radiation increase, the loss of heat mainly by the respiratory tract also increases. When the direct solar radiation exceeds 800 W m-² the production of metabolic heat of the animals also increases to the point that they can not maintain the body temperature, starting to store heat. Thus, New Sheep Sheep exposed to direct solar radiation increase latent heat loss over sensitive heat loss when direct solar radiation exceeds 800 W m-2. At warmer times, 10 to 15 h, sheep New Address maintained in the shade lose 5 to 8 W m-² and 5 to 8 W m-² by respiratory and convective airways, respectively; while those exposed to the sun lose from 6 to 12 W m-² and from 30 to 45 W m-² by respiratory and convective routes, respectively.